GIANT JUVENILE FIBROADENOMA: REPORT OF TWO CASES WITH ULTRASONOGRAPHY AND MAGNETIC RESONANCE IMAGING FINDINGS - İlkay Koray Bayrak; Zafer Özmen; Muzaffer Elmalı; Melike Kale (European Journal of Breast Health, 2008)

(untitled)
Juvenile fi broadenoma is common cause of breast masses in adolescent and young individuals. Giant fi broadenoma which is a type of fi broadenomas reaching extreme sizes in adolescent period could cause congestion and ulceration. Giant juvenile fi broadenomas are usually solitary and unilateral. With this study we discussed ultrasonographic and magnetic resonance imaging fi ndings of unilateral juvenile fi broadenomas with diameters of 10 and 12 cm.